(3cJGH GdUahGfjs - (3GdUahGfj, CHh YHO Gddg, eMeO Hf CMeO Hf YHO Gddg Hf bVGYI, cGf MkqjG (B346(3g`s ((3Ydj GdMSjfjs)
(3ChdgG (B:s
(3jbhd GdYHO MSjf (B...(3GdWHQSj(B...(3hLOJ efbhdG Yf NW GdTjN Rjf GdOjf GdTgjO GdKGfj(B...(3Yf cJGH GdJYQja(B...s
(3BNQgG (B:s
(3bdJ gPG eHfj Ydi Cf bHhd GdYHGOI HCLRGFgG ZjQ eJdGRejf(B...s
(3JHUQI GdYfhGf (B:s
(3fbhdGJ fbdgG GdTgjO GdKGfj Rjf GdOjf Yf cJGH GdJYQja ddUahGfj hLeYgG MSjf GdWHQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B76s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs